Datasets:
Tasks:
Text Generation
Modalities:
Text
Sub-tasks:
language-modeling
Languages:
English
Size:
100K - 1M
License:
needs "Library/prime.ml";; | |
parse_as_infix("**",(20,"right"));; | |
let group = new_definition | |
`group(g,(**),i,(e:A)) <=> | |
(e IN g) /\ (!x. x IN g ==> i(x) IN g) /\ | |
(!x y. x IN g /\ y IN g ==> x**y IN g) /\ | |
(!x y z. x IN g /\ y IN g /\ z IN g ==> x**(y**z) = (x**y)**z) /\ | |
(!x. x IN g ==> x**e = x /\ e**x = x) /\ | |
(!x. x IN g ==> x**i(x) = e /\ i(x)**x = e)`;; | |
let subgroup = new_definition | |
`subgroup h (g,(**),i,(e:A)) <=> h SUBSET g /\ group(h,(**),i,e)`;; | |
(* ======== translation of John's proof ==================================== *) | |
horizon := 1;; | |
let GROUP_LAGRANGE_COSETS = thm `; | |
!g h (**) i e. | |
group(g,(**),i,e:A) /\ subgroup h (g,(**),i,e) /\ FINITE g | |
==> ?q. CARD g = CARD q * CARD h /\ | |
!b. b IN g ==> ?a x. a IN q /\ x IN h /\ b = a**x | |
proof exec REWRITE_TAC[group; subgroup; SUBSET]; | |
let g h be A->bool; | |
let (**) be A->A->A; | |
let i be A->A; | |
let e be A; | |
assume e IN g; | |
assume !x. x IN g ==> i(x) IN g [1]; | |
assume !x y. x IN g /\ y IN g ==> x**y IN g [2]; | |
assume !x y z. x IN g /\ y IN g /\ z IN g | |
==> x**(y**z) = (x**y)**z [3]; | |
assume !x. x IN g ==> x**e = x /\ e**x = x [4]; | |
assume !x. x IN g ==> x**i(x) = e /\ i(x)**x = e [5]; | |
assume !x. x IN h ==> x IN g [6]; | |
assume e IN h [7]; | |
assume !x. x IN h ==> i(x) IN h [8]; | |
assume !x y. x IN h /\ y IN h ==> x**y IN h [9]; | |
assume !x y z. x IN h /\ y IN h /\ z IN h | |
==> x**(y**z) = (x**y)**z; | |
assume !x. x IN h ==> x**e = x /\ e**x = x [10]; | |
assume !x. x IN h ==> x**i(x) = e /\ i(x)**x = e [11]; | |
assume FINITE g [12]; | |
set coset = \a. {b | b IN g /\ ?x. x IN h /\ b = a**x} [coset]; | |
!a. coset a = {b' | b' IN g /\ ?x. x IN h /\ b' = a**x} [13]; | |
!a. a IN g ==> a IN coset a [14] | |
proof let a be A; | |
assume a IN g [15]; | |
?x. x IN h /\ a = a**x by 4,7; | |
qed by SIMP_TAC,13,15,IN_ELIM_THM; | |
FINITE h [16] by 6,12,FINITE_SUBSET,SUBSET; | |
!a. FINITE (coset a) | |
proof let a be A; | |
?t. FINITE t /\ coset a SUBSET t | |
proof take g; | |
qed by SIMP_TAC,12,13,IN_ELIM_THM,SUBSET; | |
qed by MATCH_MP_TAC,FINITE_SUBSET; | |
!a x y. a IN g /\ x IN g /\ y IN g /\ a**x = a**y ==> x = y [17] | |
proof let a x y be A; | |
assume a IN g /\ x IN g /\ y IN g /\ a**x = a**y [18]; | |
(i(a)**a)**x = (i(a)**a)**y by 1,3; | |
e**x = e**y by 5,18; | |
qed by 4,18; | |
!a. a IN g ==> CARD (coset a) = CARD h | |
proof let a be A; | |
assume a IN g [19]; | |
coset a = IMAGE (\x. a**x) h [20] | |
proof | |
!x. x IN g /\ (?x'. x' IN h /\ x = a**x') <=> | |
?x'. x = a**x' /\ x' IN h by 2,6; | |
qed by REWRITE_TAC,13,EXTENSION,IN_IMAGE,IN_ELIM_THM; | |
(!x y. x IN h /\ y IN h /\ a**x = a**y ==> x = y) /\ FINITE h | |
by 6,16,17,19; | |
CARD (IMAGE (\x. a**x) h) = CARD h by MATCH_MP_TAC,CARD_IMAGE_INJ; | |
qed by 20; | |
!x y. x IN g /\ y IN g ==> i(x**y) = i(y)**i(x) [21] | |
proof let x y be A; | |
assume x IN g /\ y IN g [22]; | |
?a. a IN g /\ i(x**y) IN g /\ i(y)**i(x) IN g /\ | |
a**i(x**y) = a**i(y)**i(x) | |
proof take x**y; | |
e = x**(y**i(y))**i(x) by 1,4,5,22; | |
.= ((x**y)**i(y))**i(x) by 1,2,3,22; | |
qed by SIMP_TAC,1,2,3,5,22; | |
qed by 17; | |
!x. x IN g ==> i(i(x)) = x [23] | |
proof let x be A; | |
assume x IN g; | |
?a. a IN g /\ i(i(x)) IN g /\ x IN g /\ a**i(i(x)) = a**x | |
proof take i(x); | |
qed by 1,5; | |
qed by MATCH_MP_TAC,17; | |
!a b. a IN g /\ b IN g | |
==> coset a = coset b \/ coset a INTER coset b = {} | |
proof let a b be A; | |
assume a IN g /\ b IN g [24]; | |
cases; | |
suppose i(b)**a IN h [25]; | |
now let x be A; | |
!x. x IN h ==> b**(i(b)**a)**x = a**x /\ a**i(i(b)**a)**x = b**x | |
by SIMP_TAC,1,3,4,5,6,21,23,24; | |
thus x IN g /\ (?x'. x' IN h /\ x = a**x') <=> | |
x IN g /\ (?x'. x' IN h /\ x = b**x') by 8,9,25; | |
end; | |
coset a = coset b by REWRITE_TAC,13,EXTENSION,IN_ELIM_THM; | |
qed; | |
suppose ~(i(b)**a IN h) [26]; | |
now let x be A; | |
assume x IN g /\ (?y. y IN h /\ x = a**y) /\ (?z. z IN h /\ x = b**z); | |
consider y z such that y IN h /\ x = a**y /\ z IN h /\ x = b**z [27]; | |
(i(b)**a)**y = i(b)**a**y by 1,3,6,24,27; | |
.= i(b)**b**z by 27; | |
.= e**z by 1,3,5,6,24,27; | |
.= z by 10,27; | |
z**i(y) = ((i(b)**a)**y)**i(y); | |
.= (i(b)**a)**y**i(y) by 1,2,3,5,6,24,27; | |
.= (i(b)**a)**e by 11,27; | |
.= i(b)**a by 1,2,4,24; | |
thus F by 8,9,26,27; | |
end; | |
!x. ~((x IN g /\ ?y. y IN h /\ x = a**y) /\ | |
(x IN g /\ ?z. z IN h /\ x = b**z)); | |
coset a INTER coset b = {} | |
by REWRITE_TAC,13,EXTENSION,NOT_IN_EMPTY,IN_INTER,IN_ELIM_THM; | |
qed; | |
end; | |
set q = {c | ?a. a IN g /\ c = (@)(coset a)} [q] [28]; take q; | |
!b. b IN g ==> ?a x. a IN q /\ x IN h /\ b = a**x [29] | |
proof let b be A; | |
assume b IN g [30]; | |
set C = (@)(coset b) [C] [31]; take C; | |
(@)(coset b) IN {c | ?a. a IN g /\ c = (@)(coset a)} by 30; | |
thus C IN q by q,C; | |
C IN coset b by 14,30,C,IN,SELECT_AX; | |
C IN {b' | b' IN g /\ ?x. x IN h /\ b' = b**x} by 13; | |
consider c such that | |
C IN g /\ c IN h /\ C = b**c [32]; | |
take i(c); | |
(b**c)**i(c) = b**c**i(c) by 1,3,6,30; | |
.= b by 1,4,5,6,30,32; | |
qed by 8,32; | |
!a b. a IN g /\ b IN g /\ a IN coset b ==> b IN coset a [33] | |
proof let a b be A; | |
a IN g /\ b IN g /\ a IN g /\ (?x. x IN h /\ a = b**x) | |
==> b IN g /\ (?x. x IN h /\ b = a**x) | |
proof | |
assume a IN g /\ b IN g /\ a IN g /\ ?x. x IN h /\ a = b**x [34]; | |
thus b IN g; | |
consider c such that c IN h /\ a = b**c by 34; | |
take i(c); | |
qed by 3,4,6,8,11,34; | |
qed by REWRITE_TAC,13,IN_ELIM_THM; | |
!a b c. a IN coset b /\ b IN coset c /\ c IN g ==> a IN coset c [35] | |
proof let a b c be A; | |
now assume (a IN g /\ ?x. x IN h /\ a = b**x) /\ | |
(b IN g /\ ?x. x IN h /\ b = c**x) /\ c IN g [36]; | |
consider x x' such that x IN h /\ a = b**x /\ x' IN h /\ b = c**x'; | |
thus a IN g /\ ?x. x IN h /\ a = c**x by 3,6,9,36; | |
end; | |
qed by REWRITE_TAC,13,IN_ELIM_THM; | |
!a b. a IN coset b ==> a IN g [37] | |
proof let a b be A; | |
a IN g /\ (?x. x IN h /\ a = b**x) ==> a IN g; | |
qed by REWRITE_TAC,13,IN_ELIM_THM; | |
!a b. a IN coset b /\ b IN g ==> coset a = coset b [38] | |
by 33,35,37,EXTENSION; | |
!a. a IN g ==> (@)(coset a) IN coset a [39] by 14,IN,SELECT_AX; | |
!a. a IN q ==> a IN g [40] | |
proof let a be A; assume a IN q; | |
a IN {c | ?a. a IN g /\ c = (@)(coset a)} by q; | |
consider a' such that a' IN g /\ a = (@)(coset a'); | |
qed by 37,39; | |
!a x a' x'. a IN q /\ a' IN q /\ x IN h /\ x' IN h /\ a'**x' = a**x | |
==> a' = a /\ x' = x [41] | |
proof let a x a' x' be A; | |
assume a IN q /\ a' IN q /\ x IN h /\ x' IN h /\ a'**x' = a**x [42]; | |
a IN {c | ?a. a IN g /\ c = (@)(coset a)} /\ | |
a' IN {c | ?a. a IN g /\ c = (@)(coset a)} by q; | |
consider a1 a2 such that | |
a1 IN g /\ a = (@)(coset a1) /\ a2 IN g /\ a' = (@)(coset a2) [43]; | |
a IN g /\ a' IN g [44] by 37,39; | |
coset a = coset a1 /\ coset a' = coset a2 by 38,39,43; | |
a = (@)(coset a) /\ a' = (@)(coset a') [45] by 43; | |
?x. x IN h /\ a' = a**x | |
proof take x**i(x'); | |
thus x**i(x') IN h by 8,9,42; | |
a' = a'**x'**i(x') by 4,5,6,42,44; | |
.= (a**x)**i(x') by 1,2,3,6,42,44; | |
qed by 1,2,3,6,42,44; | |
a' IN coset a by REWRITE_TAC,13,44,IN_ELIM_THM; | |
coset a = coset a' by 38,44; | |
qed by 6,17,42,44,45; | |
g = IMAGE (\(a,x). a**x) {(a,x) | a IN q /\ x IN h} | |
proof | |
!x. x IN g <=> ?p1 p2. (x = p1**p2 /\ p1 IN q) /\ p2 IN h by 2,6,29,40; | |
qed by REWRITE_TAC,EXTENSION,IN_IMAGE,IN_ELIM_THM,EXISTS_PAIR_THM,PAIR_EQ, | |
CONJ_ASSOC,ONCE_REWRITE_RULE[CONJ_SYM] UNWIND_THM1; | |
CARD g = CARD (IMAGE (\(a,x). a**x) {(a,x) | a IN q /\ x IN h}) [46]; | |
.= CARD {(a,x) | a IN q /\ x IN h} | |
proof | |
!x y. x IN {(a,x) | a IN q /\ x IN h} /\ | |
y IN {(a,x) | a IN q /\ x IN h} /\ | |
(\(a,x). a**x) x = (\(a,x). a**x) y | |
==> x = y [47] | |
proof | |
!p1 p2 p1' p2'. (?a x. (a IN q /\ x IN h) /\ p1 = a /\ p2 = x) /\ | |
(?a x. (a IN q /\ x IN h) /\ p1' = a /\ p2' = x) /\ | |
p1**p2 = p1'**p2' | |
==> p1 = p1' /\ p2 = p2' by 41; | |
qed by REWRITE_TAC,FORALL_PAIR_THM,IN_ELIM_THM,PAIR_EQ; | |
FINITE q /\ FINITE h by 6,12,40,FINITE_SUBSET,SUBSET; | |
FINITE {(a,x) | a IN q /\ x IN h} by FINITE_PRODUCT; | |
qed by MATCH_MP_TAC CARD_IMAGE_INJ,47; | |
.= CARD q * CARD h by 6,12,40,46,CARD_PRODUCT,FINITE_SUBSET,SUBSET; | |
qed by 29`;; | |
let GROUP_LAGRANGE = thm `; | |
!g h (**) i e. | |
group (g,( ** ),i,e:A) /\ subgroup h (g,(**),i,e) /\ FINITE g | |
==> CARD h divides CARD g | |
by GROUP_LAGRANGE_COSETS,DIVIDES_LMUL,DIVIDES_REFL`;; | |
(* ======== and formal proof sketch derived from this translation ========== *) | |
horizon := -1;; | |
let GROUP_LAGRANGE_COSETS_SKETCH = ref None;; | |
GROUP_LAGRANGE_COSETS_SKETCH := Some `; | |
!g h (**) i e. | |
group(g,(**),i,e:A) /\ subgroup h (g,(**),i,e) /\ FINITE g | |
==> ?q. CARD g = CARD q * CARD h /\ | |
!b. b IN g ==> ?a x. a IN q /\ x IN h /\ b = a**x | |
proof exec REWRITE_TAC[group; subgroup; SUBSET]; | |
let g h be A->bool; | |
let (**) be A->A->A; | |
let i be A->A; | |
let e be A; | |
assume e IN g; | |
assume !x. x IN g ==> i(x) IN g; | |
assume !x y. x IN g /\ y IN g ==> x**y IN g; | |
assume !x y z. x IN g /\ y IN g /\ z IN g | |
==> x**(y**z) = (x**y)**z; | |
assume !x. x IN g ==> x**e = x /\ e**x = x; | |
assume !x. x IN g ==> x**i(x) = e /\ i(x)**x = e; | |
assume !x. x IN h ==> x IN g; | |
assume e IN h; | |
assume !x. x IN h ==> i(x) IN h; | |
assume !x y. x IN h /\ y IN h ==> x**y IN h; | |
assume !x y z. x IN h /\ y IN h /\ z IN h | |
==> x**(y**z) = (x**y)**z; | |
assume !x. x IN h ==> x**e = x /\ e**x = x; | |
assume !x. x IN h ==> x**i(x) = e /\ i(x)**x = e; | |
assume FINITE g; | |
set coset = \a. {b | b IN g /\ ?x. x IN h /\ b = a**x}; | |
!a. coset a = {b' | b' IN g /\ ?x. x IN h /\ b' = a**x}; | |
!a. a IN g ==> a IN coset a | |
proof let a be A; | |
assume a IN g; | |
?x. x IN h /\ a = a**x; | |
qed; | |
FINITE h; | |
:: #1 | |
:: 1: inference error | |
!a. FINITE (coset a) | |
proof let a be A; | |
?t. FINITE t /\ coset a SUBSET t | |
proof take g; | |
qed; | |
:: #2 | |
:: 2: inference time-out | |
qed; | |
:: #2 | |
!a x y. a IN g /\ x IN g /\ y IN g /\ a**x = a**y ==> x = y | |
proof let a x y be A; | |
assume a IN g /\ x IN g /\ y IN g /\ a**x = a**y; | |
(i(a)**a)**x = (i(a)**a)**y; | |
e**x = e**y; | |
:: #2 | |
qed; | |
!a. a IN g ==> CARD (coset a) = CARD h | |
proof let a be A; | |
assume a IN g; | |
coset a = IMAGE (\x. a**x) h | |
proof | |
!x. x IN g /\ (?x'. x' IN h /\ x = a**x') <=> | |
?x'. x = a**x' /\ x' IN h; | |
qed; | |
:: #2 | |
(!x y. x IN h /\ y IN h /\ a**x = a**y ==> x = y) /\ FINITE h; | |
CARD (IMAGE (\x. a**x) h) = CARD h; | |
:: #2 | |
qed; | |
!x y. x IN g /\ y IN g ==> i(x**y) = i(y)**i(x) | |
proof let x y be A; | |
assume x IN g /\ y IN g; | |
?a. a IN g /\ i(x**y) IN g /\ i(y)**i(x) IN g /\ | |
a**i(x**y) = a**i(y)**i(x) | |
proof take x**y; | |
e = x**(y**i(y))**i(x); | |
:: #2 | |
.= ((x**y)**i(y))**i(x); | |
:: #2 | |
qed; | |
qed; | |
!x. x IN g ==> i(i(x)) = x | |
proof let x be A; | |
assume x IN g; | |
?a. a IN g /\ i(i(x)) IN g /\ x IN g /\ a**i(i(x)) = a**x | |
proof take i(x); | |
qed; | |
qed; | |
!a b. a IN g /\ b IN g | |
==> coset a = coset b \/ coset a INTER coset b = {} | |
proof let a b be A; | |
assume a IN g /\ b IN g; | |
cases; | |
suppose i(b)**a IN h; | |
now let x be A; | |
!x. x IN h ==> b**(i(b)**a)**x = a**x /\ a**i(i(b)**a)**x = b**x; | |
:: #2 | |
thus x IN g /\ (?x'. x' IN h /\ x = a**x') <=> | |
x IN g /\ (?x'. x' IN h /\ x = b**x'); | |
:: #2 | |
end; | |
coset a = coset b; | |
:: #2 | |
qed; | |
suppose ~(i(b)**a IN h); | |
now let x be A; | |
assume x IN g /\ (?y. y IN h /\ x = a**y) /\ (?z. z IN h /\ x = b**z); | |
consider y z such that y IN h /\ x = a**y /\ z IN h /\ x = b**z; | |
(i(b)**a)**y = i(b)**a**y; | |
.= i(b)**b**z; | |
.= e**z; | |
:: #2 | |
.= z; | |
z**i(y) = ((i(b)**a)**y)**i(y); | |
.= (i(b)**a)**y**i(y); | |
:: #2 | |
.= (i(b)**a)**e; | |
.= i(b)**a; | |
:: #2 | |
thus F; | |
:: #2 | |
end; | |
!x. ~((x IN g /\ ?y. y IN h /\ x = a**y) /\ | |
(x IN g /\ ?z. z IN h /\ x = b**z)); | |
coset a INTER coset b = {}; | |
:: #2 | |
qed; | |
end; | |
set q = {c | ?a. a IN g /\ c = (@)(coset a)}; | |
take q; | |
!b. b IN g ==> ?a x. a IN q /\ x IN h /\ b = a**x | |
proof let b be A; | |
assume b IN g; | |
set C = (@)(coset b); | |
take C; | |
(@)(coset b) IN {c | ?a. a IN g /\ c = (@)(coset a)}; | |
thus C IN q; | |
C IN coset b; | |
:: #2 | |
C IN {b' | b' IN g /\ ?x. x IN h /\ b' = b**x}; | |
consider c such that | |
C IN g /\ c IN h /\ C = b**c; | |
take i(c); | |
(b**c)**i(c) = b**c**i(c); | |
.= b; | |
qed; | |
!a b. a IN g /\ b IN g /\ a IN coset b ==> b IN coset a | |
proof let a b be A; | |
a IN g /\ b IN g /\ a IN g /\ (?x. x IN h /\ a = b**x) | |
==> b IN g /\ (?x. x IN h /\ b = a**x) | |
proof | |
assume a IN g /\ b IN g /\ a IN g /\ ?x. x IN h /\ a = b**x; | |
thus b IN g; | |
consider c such that c IN h /\ a = b**c; | |
take i(c); | |
qed; | |
:: #2 | |
qed; | |
!a b c. a IN coset b /\ b IN coset c /\ c IN g ==> a IN coset c | |
proof let a b c be A; | |
now assume (a IN g /\ ?x. x IN h /\ a = b**x) /\ | |
(b IN g /\ ?x. x IN h /\ b = c**x) /\ c IN g; | |
consider x x' such that x IN h /\ a = b**x /\ x' IN h /\ b = c**x'; | |
thus a IN g /\ ?x. x IN h /\ a = c**x; | |
:: #2 | |
end; | |
qed; | |
:: #2 | |
!a b. a IN coset b ==> a IN g | |
proof let a b be A; | |
a IN g /\ (?x. x IN h /\ a = b**x) ==> a IN g; | |
qed; | |
!a b. a IN coset b /\ b IN g ==> coset a = coset b; | |
:: #2 | |
!a. a IN g ==> (@)(coset a) IN coset a; | |
:: #2 | |
!a. a IN q ==> a IN g | |
proof let a be A; | |
assume a IN q; | |
a IN {c | ?a. a IN g /\ c = (@)(coset a)}; | |
consider a' such that a' IN g /\ a = (@)(coset a'); | |
qed; | |
!a x a' x'. a IN q /\ a' IN q /\ x IN h /\ x' IN h /\ a'**x' = a**x | |
==> a' = a /\ x' = x | |
proof let a x a' x' be A; | |
assume a IN q /\ a' IN q /\ x IN h /\ x' IN h /\ a'**x' = a**x; | |
a IN {c | ?a. a IN g /\ c = (@)(coset a)} /\ | |
a' IN {c | ?a. a IN g /\ c = (@)(coset a)}; | |
consider a1 a2 such that | |
a1 IN g /\ a = (@)(coset a1) /\ a2 IN g /\ a' = (@)(coset a2); | |
:: #2 | |
a IN g /\ a' IN g; | |
coset a = coset a1 /\ coset a' = coset a2; | |
:: #2 | |
a = (@)(coset a) /\ a' = (@)(coset a'); | |
?x. x IN h /\ a' = a**x | |
proof take x**i(x'); | |
thus x**i(x') IN h; | |
:: #2 | |
a' = a'**x'**i(x'); | |
:: #2 | |
.= (a**x)**i(x'); | |
:: #2 | |
qed; | |
:: #2 | |
a' IN coset a; | |
:: #2 | |
coset a = coset a'; | |
qed; | |
:: #2 | |
g = IMAGE (\(a,x). a**x) {(a,x) | a IN q /\ x IN h} | |
proof | |
!x. x IN g <=> ?p1 p2. (x = p1**p2 /\ p1 IN q) /\ p2 IN h; | |
:: #2 | |
qed; | |
:: #2 | |
CARD g = CARD (IMAGE (\(a,x). a**x) {(a,x) | a IN q /\ x IN h}); | |
.= CARD {(a,x) | a IN q /\ x IN h} | |
proof | |
!x y. x IN {(a,x) | a IN q /\ x IN h} /\ | |
y IN {(a,x) | a IN q /\ x IN h} /\ | |
(\(a,x). a**x) x = (\(a,x). a**x) y | |
==> x = y | |
proof | |
!p1 p2 p1' p2'. (?a x. (a IN q /\ x IN h) /\ p1 = a /\ p2 = x) /\ | |
(?a x. (a IN q /\ x IN h) /\ p1' = a /\ p2' = x) /\ | |
p1**p2 = p1'**p2' | |
==> p1 = p1' /\ p2 = p2'; | |
qed; | |
:: #2 | |
FINITE q /\ FINITE h; | |
:: #2 | |
FINITE {(a,x) | a IN q /\ x IN h}; | |
:: #2 | |
qed; | |
:: #2 | |
.= CARD q * CARD h; | |
:: #2 | |
qed`;; | |